Developing English for Specific Purposes Material: English for Wetlands at Lambung Mangkurat University - Emma Rosana Febriyanti; Raisa Fadilla; Fahmi Hidayat (Universitas Bengkulu, 2022)
Referring to Lambung Mangkurat University's (ULM) policy to become the center of Asia-Pacific wetland development in 2027, one of the efforts made is to improve the ability of ULM students, especially in English language skills related to wetlands. In this regard, this research was conducted to develop online English-based materials on Wetlands. This research aims to meet the needs of ULM students and assist ULM lecturers in teaching courses related to wetlands. The development method used in the study was adapted from Dick and Carey (2001), which includes (1) needs analysis, (2) material development, (3) validation and revision. The results showed that the online-based English for Wetlands material that was developed met the criteria of validity, practicality, and effectiveness. With the development of this material, it is hoped that lecturers and students can carry out independent learning related to wetlands.